2009
DOI: 10.1248/bpb.32.1204
|View full text |Cite
|
Sign up to set email alerts
|

First Indications Demonstrating the Preventive Effects of NZ-419, a Novel Intrinsic Antioxidant, on the Initiation and/or Progression of Chronic Renal Failure in Rats

Abstract: Although the number of patients with end-stage renal disease (ESRD) has increased rapidly over the last three decades and, prior to the advent of dialysis, some treatments including dietary control, drug therapy with a spherical carbonaceous absorbent, and anti-hypertensive drugs including ACEIs (angiotensin converting enzyme inhibitors) and ARBs (angiotensin receptor blockades) have shown some inhibition of the progression of chronic kidney disease (CKD) and chronic renal failure (CRF), these treatments are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…1) Stages of CRF patients are shown to be 3, 4, or 5: eGFR of these are 30-59, 15-29, or Ͻ15 ml/min/1.73 cm 3 , respectively. Since the clinical eGFR 0 has been shown to be ca.…”
Section: Estimation Of Gfr For Ratsmentioning
confidence: 99%
See 3 more Smart Citations
“…1) Stages of CRF patients are shown to be 3, 4, or 5: eGFR of these are 30-59, 15-29, or Ͻ15 ml/min/1.73 cm 3 , respectively. Since the clinical eGFR 0 has been shown to be ca.…”
Section: Estimation Of Gfr For Ratsmentioning
confidence: 99%
“…1) In our previous paper, 3) we reported for the first time that an intrinsic antioxidant compound could prevent the initiation and/or progression of CRF: the compound investigated was NZ-419 (5-hydroxy-1-methylimidazolidine-2,4-dione, 5-hydroxy-1-methylhydantoin: HMH, CAS: 84210-26-4), [4][5][6][7][8][9] a creatinine (Cr) metabolite that prevented the initiation and/or progression of adenine-induced CRF. We chose CRF or CKD at stages equivalent to human stages 3, 4 and 5, where hydroxyl radicals are over-produced, 2,10) as one of the targets aims, 3,11,12) because NZ-419 had been shown to be a hydroxyl radical scavenger. 11,12) Meanwhile, since there is a hypothesis that oxidative stress might be a common key factor in the progression of CRF induced by several different causes, antioxidants might inhibit the progression of CRF regardless of its causes.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…However, in recent years, many studies have shown that their metabolites are involved in the progression of kidney disease. Creatinine is converted to creatinine hydroxide in the presence of free radicals, 13 eventually generating methylguanidine which is more toxic, 14 which increases the expression of TGF-b1, CTGF and FN in renal tubular epithelial cells and exacerbates renal tubular interstitial fibrosis. 15 In this way, creatinine indirectly promotes fibrosis.…”
Section: Discussionmentioning
confidence: 99%